1989
DOI: 10.1002/mus.880121111
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatigue in some neurological disorders

Abstract: Fatigue of tibialis anterior (TA) was induced by repetitive electrical stimulation. Using this test, patients with upper motor neuron muscle weakness owing to multiple sclerosis (MS) and injuries to the spinal cord showed greater fatigability of their TA muscles, suggesting that the muscle fiber population changed toward that typical of fatigable motor units. During repetitive stimulation, in addition to the decrement in tension there was an increase in half-relaxation time of tetanic contractions at 40 Hz in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 8 publications
2
42
0
4
Order By: Relevance
“…24,29,33 Because both CMAP and maximum force in part reflect muscle size, it is possible that the preexercise reductions of CMAP amplitude, MVC, and stimulated force observed in the patients may have been the result of differences in muscle size. Differences in muscle size between groups may have been due to disuse atrophy in MS or difference in sex distribution between the two groups.…”
Section: Preexercise Alterations In Muscle Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…24,29,33 Because both CMAP and maximum force in part reflect muscle size, it is possible that the preexercise reductions of CMAP amplitude, MVC, and stimulated force observed in the patients may have been the result of differences in muscle size. Differences in muscle size between groups may have been due to disuse atrophy in MS or difference in sex distribution between the two groups.…”
Section: Preexercise Alterations In Muscle Propertiesmentioning
confidence: 99%
“…34,35 Previous studies have shown that peripheral sources of fatigue are also important in spastic muscles. 24,29 Lenman et al suggested secondary changes in spastic muscles are similar to those of immobilization and disuse. 24 In another study of a small number of patients with various types of spastic paraparesis, greater changes in energy metabolites accompanied the excessive muscle fatigue observed in patients compared to controls, which suggested that intramuscular factors may contribute to fatigue in spastic paraparesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater volume may be due to an increased proportion of type 2 fibers on this side, which are known to have greater cross-sectional area. While it is suggested that muscle characteristics of patients with MS shift to a higher proportion of type 2 fibers [24,[30][31], impaired neural drive to the muscles may prevent increased strength. However, it is likely that the shift in fiber type characteristics on one side of the body is not sufficient to cause imbalanced muscle volume.…”
Section: Discussionmentioning
confidence: 99%
“…Утомляемость может проявляться отсутствием физической и психической энергии, неконтролируемой апатией, иногда утомляе-мостью отдельных мышечных групп при повторяющихся движениях [12].…”
unclassified